Mucosal-Associated Invariant T Cells: New Insights into Antigen Recognition and Activation - Xingxing Xiao; Xingxing Xiao; Jianping Cai; Jianping Cai (Frontiers in Immunology, 2017)
Mucosal-associated invariant T (MAIT) cells, a novel subpopulation of innate-like T cells that express an invariant T cell receptor (TCR)α chain and a diverse TCRβ chain, can recognize a distinct set of small molecules, vitamin B metabolites, derived from some bacteria, fungi but not viruses, in the context of an evolutionarily conserved major histocompatibility complex-related molecule 1 (MR1). This implies that MAIT cells may play unique and important roles in host immunity. Although viral antigens are not recognized by this limited TCR repertoire, MAIT cells are known to be activated in a TCR-independent mechanism during some viral infections, such as hepatitis C virus and influenza virus. In this article, we will review recent works in MAIT cell antigen recognition, activation and the role MAIT cells may play in the process of bacterial and viral infections and pathogenesis of non-infectious diseases.